Chain‐growth polycondensation via the substituent effect: Investigation of the monomer structure on synthesis of poly(N‐octyl‐benzamide). Issue 17 (11th August 2020) - Prehn, Frederick C.; Etz, Brian D.; Reese, Caleb J.; Vyas, Shubham; Boyes, Stephen G.
Abstract: A systematic study of the behavior of different leaving groups on a variety of ester‐based monomers was performed for the chain‐growth polycondensation synthesis of poly(N‐octyl benzamide). Linear and branched alkane esters were compared with their phenyl analogs using both computational and experimental methods. Kinetic experiments along with qualitative solubility observations were used, with the aid of nuclear magnetic resonance spectroscopy and gel‐permeation chromatography, to determine progress of the reaction, molecular weights, and molecular weight distributions. It was found that the reactivity of the monomer's ester group depends more on the stability of the leaving alkoxide than the electrophilicity of the carbonyl carbon, which contradicts previous literature. The order of reactivity increases for the alkyl esters with decreasing steric hindrance and decreasing pKa of the substituent. For the phenyl ester derivatives, the more electron withdrawing character of a para substituent increases the reactivity of the ester group, due to the higher resonance stabilization of the leaving phenoxide anion, not due to an increase in the electrophilicity of the carbonyl carbon. Abstract : A detailed study into the chain‐growth polycondensation reaction for the synthesis of poly(N‐octyl‐benzamide) is conducted. Through experimental and computational results, it is demonstrated that the basicity of the monomer leaving group plays a dominant role in establishing a well‐controlled polymerization.